Watershed Assessment for River Stability and Sediment Supply Applied to Wildcat Creek Watershed in Riley County, Kansas - Buffington, Jared; Clark, Jeffrey; Denlinger, Danielle; Engelke, Jennifer; Musoke, Elizabeth; Stout, Breanna; Sullivan, Justine; Tucker, Terry; Barnes, Philip L.; Sanders, Christopher (Dept. of Landscape Architecture and Regional and Community Planning. Kansas State University, 2012)
Wildcat Creek Watershed (approx. 99 square miles) in Riley County, Kansas had significant flooding in recent years. A Watershed Assessment of River Stability and Sediment Supply (WARSSS, Rosgen, 2006) of Wildcat Creek was performed to determine locations that are contributing to the flooding. WARSSS is split into three levels: Reconnaissance Level Assessment (RLA), Rapid Resource Inventory for Sediment and Stability Consequence (RRISSC), and Prediction Level Assessment (PLA). The assessment for Wildcat Creek completed to date focuses on the first two phases, RLA and RRISSC evaluations. The RLA level focuses on creating sections by similar land use and land cover to get an overall understanding of the watershed. The RRISSC level divides the watershed into nineteen sub-watersheds and takes a more detailed approach to the assessment. The WARSSS assessment is typically done on smaller watershed scale, but was adapted to encompass the entire Wildcat Creek Watershed. The assessment provided the foundation for six masters reports. The reports focused on potential solutions to the flooding and improving Wildcat Creek Watershed.
Keywords: Wildcat Creek; Riley County; Watershed assessment; River stability; Sediment supply; Flooding; WARSSS